2018
DOI: 10.1002/ptr.6131
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of vaginal suppository based on myrtle in patients with cervicovaginal human papillomavirus infection: A randomized, double‐blind, placebo trial

Abstract: Human papillomavirus (HPV) can be detected in most of cervical cancers. Due to antiviral, antimutagenic, and proapoptotic activities of myrtle, this study was designed to investigate the effect of a herbal suppository based on myrtle in cervicovaginal HPV infections. This study was performed as a double-blind randomized trial at the Clinic of Traditional Medicine in Mashhad University of Medical Sciences between 2016 and 2017. Sixty women, 18 to 50 years old, with cervicovaginal HPV infection, were included an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…Many studies showed the direct action against cell-free virions, the broad-spectrum antiviral activities and the antiviral versatility of EOs. The antiviral potency was tested in clinical studies [61,62] and some achieved pleasant results. As an example, myrtle vaginal suppository containing 0.5% myrtle EO was effective in patients with HPV infection with an HPV clearance rate of 92.6% compared with that of placebo (68%) [62].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies showed the direct action against cell-free virions, the broad-spectrum antiviral activities and the antiviral versatility of EOs. The antiviral potency was tested in clinical studies [61,62] and some achieved pleasant results. As an example, myrtle vaginal suppository containing 0.5% myrtle EO was effective in patients with HPV infection with an HPV clearance rate of 92.6% compared with that of placebo (68%) [62].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…The antiviral potency was tested in clinical studies [61,62] and some achieved pleasant results. As an example, myrtle vaginal suppository containing 0.5% myrtle EO was effective in patients with HPV infection with an HPV clearance rate of 92.6% compared with that of placebo (68%) [62]. Taken together, EOs hold promise as candidates for prophylactic and therapeutic treatment of virus-induced diseases in future.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…However, the mean PFAS concentrations in tampons (made of cotton, rayon, or a blend of them) were below the LOQs, which may be due to the fact that tampons must maintain a high water absorption capacity and thus perhaps no fluorinated compounds are used in the production process. As for bactericidal liquids, the ingredients are mainly composed of some components from Chinese herbal medicines (e.g., Radix Sophorae Flavescenti and Phellodendri Cortex ) . The reason for the few PFAS detected in bactericidal liquids may be that they are primarily used for vulva cleaning and as bacteriostatic agents and they do not require any waterproofing feature.…”
Section: Resultsmentioning
confidence: 99%
“…The myrtle efficiency for vaginal suppositories in patients with cervicovaginal human papillomavirus (HPV) infection was investigated [ 54 ]. The results showed that the myrtle vaginal suppository was effective in HPV clearance compared with placebo.…”
Section: Biological and Pharmaceutical Activities Of Myrtlementioning
confidence: 99%